Análisis A Los Estados Financieros En Multillantas Adolfo Del Cantón Piñas, Período 2013 - 2014 - Núñez Feijóo, Silvana Esther (2016)
The work of thesis named ANALYSIS To THE FINANCIAL STATEMENTS IN MULTI-TIRES ADOLPH of the CANTON PIÑAS, PERIOD 2013 -2014, it was developed with the fundamental objective to accomplish a process, allowing evaluating the financial economic situation, what affects definitively to the owner in the decision making for the correct administration of the company. On the basis of the realistic brand-name drugs proposed in the project, , is orients to perform the analysis vertical and horizontal where is determined the participation of each an of them accounts and establishing the variation absolute and relative that has suffered each departure of the financial statements, demonstrating that in the year 2014 your values decreased what comes from great contribution, since is will have less obligations for pay, and is may finance better the capital of work of the company. Another one of the objectives is the application of the financial indexes I eat: Liquidity, solvency, debt and profitability to know the company performance and a report of financial statement analysis finally generates itself in the one that it becomes evident in results. In conclusion it is determined that in the year 2014 income from sales, cost and expenses diminished, and whereby they maintain a tall level of merchandise and a low inventory turnover in spite of the fact that benefit generates what is recommended to the owner is qualifying the employees to improve the sale of the product and that way obtaining economic return.